The Strategic Rivalry Between Turkey and Iran and Its Implications for the Middle East - Matar, Ali Khidr (Journal of Economic, Administrative and Legal Sciences, 2025)
This research aims to analyze the nature of the strategic competition between Turkey and Iran in the Middle East and its impact on regional stability from 2003 to the present. The study's central problem is that this competition, while historically rooted, has taken on new and complex dimensions following the 2003 U.S. invasion of Iraq. This event acted as a catalyst, deepening existing crises and destabilizing the region.Adopting a descriptive-analytical methodology, the study seeks to test three core hypotheses. First, it posits that the strategic competition between the two powers is driven by the goal of filling the security and political vacuum in the region, which paradoxically leads to increased instability rather than balance. Second, it argues that Turkey and Iran utilize divergent mechanisms in their rivalry: Turkey predominantly leverages soft power and economic tools, while Iran relies more on its network of military proxies and ideological support. Third, the study hypothesizes that this competition has exacerbated sectarian and political divisions in conflict zones like Syria and Iraq, prolonging these conflicts.The study's objectives are multifaceted. They include identifying the historical, ideological, and security-based drivers of the competition; analyzing its primary arenas, such as Syria and Iraq; examining the tools and mechanisms each country employs to extend its influence; and assessing the direct and indirect impact of the rivalry on regional security. The research also aims to outline potential future scenarios for the relationship between Turkey and Iran and their implications for the regional balance of power.This research holds significant academic and practical value. It helps to fill a gap in the Arabic literature that addresses this subject in depth, while also offering a practical framework for analyzing the dynamics of competition between regional powers. The findings could be valuable to policymakers, aiding them in understanding the true dimensions of these crises and formulating more effective strategies.
Keywords: Strategic Competition; Turkish Competition; Iranian Competition; Middle East